Stella Artois in South Africa : cause marketing and the building of a global brand - Hennessy, Julie, (SAGE Business Cases., 2019)
Stella Artois, an AB InBev brand, is the world's best-selling Belgian beer. In early 2017, Ricardo Tadeu, AB InBev Zone President for Africa, is planning the brand's entry into its next export market: South Africa. The case explores Stella's introduction strategies into three of its export markets—the UK (1976), the US (2000), and Mexico (2016)—examining the drivers of the brand's success as well as its failures. Students will analyze the brand's previous launches to determine what made it successful in some markets and not in others. They will apply these learnings to develop a strategy for the brand's introduction to the South African market. Beyond the central discussion of growth through international expansion, the case addresses issues of brand positioning for premium products, changing consumer perceptions, the use of cause marketing, category development and maturity, and competitive strategy.